1999
DOI: 10.1152/ajpendo.1999.277.1.e144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nonsulfur and sulfur amino acids on the regulation of hepatic enzymes of cysteine metabolism

Abstract: To determine the role of nonsulfur vs. sulfur amino acids in regulation of cysteine metabolism, rats were fed a basal diet or diets supplemented with a mixture of nonsulfur amino acids (AA), sulfur amino acids (SAA), or both for 3 wk. Hepatic cysteine-sulfinate decarboxylase (CSDC), cysteine dioxygenase (CDO), and γ-glutamylcysteine synthetase (GCS) activity, concentration, and mRNA abundance were measured. Supplementation with AA alone had no effect on any of these measures. Supplementation of the basal diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
55
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 23 publications
9
55
1
Order By: Relevance
“…In the wild-type animal, hepatic metabolism of cysteine is responsible for the majority of taurine synthesis (3,4,13). In the CDO Ϫ/Ϫ mouse, tissue and plasma taurine concentrations were reduced to less than 10% of wild-type levels (30).…”
Section: Discussionmentioning
confidence: 99%
“…In the wild-type animal, hepatic metabolism of cysteine is responsible for the majority of taurine synthesis (3,4,13). In the CDO Ϫ/Ϫ mouse, tissue and plasma taurine concentrations were reduced to less than 10% of wild-type levels (30).…”
Section: Discussionmentioning
confidence: 99%
“…2) (6,15,23). With the recent discovery of a cross-linked cofactor in the active site of CDO, we hypothesized that the difference in migration could be due to two separate populations of CDO protein as follows: one population containing the internal cross-link and the other lacking the cross-link.…”
Section: Resolution Of Non-cofactor-and Cofactor-containing Species Omentioning
confidence: 99%
“…Cofactor Biosynthesis Depends upon Substrate and Catalytic Turnover-Several previous studies have demonstrated that the lower cofactor-containing band of hepatic CDO protein is highly expressed when rats are fed diets that are rich in cysteine or cysteine precursors (6,23). We further examined the course of this expression in vivo by switching rats that had been sustained for 14 days on a low protein diet (i.e.…”
mentioning
confidence: 99%
“…Additionally, in vivo kinetic experiments in normal adults have shown that GSH turnover is suppressed by diets deficient in sulfur amino acids (28) and by diets with marginal amounts of protein (21). Similarly, in animal models, dietary deficiencies of the precursor amino acids, especially cysteine, resulted in decreased GSH concentrations (4,10,15,24). Therefore, it is plausible that substrate availability may constrain the in vivo synthesis of GSH in SCD, resulting in low GSH concentrations.…”
mentioning
confidence: 99%